Tipología de la formación inicial del profesorado de EFTP en Alemania - Porcher, Christoph; Trampe, Kristina (Universidad de Costa Rica, 2024)
The discourse on Technical and Vocational Education and Training (TVET) teacher education in Germany is dominated by the high demand for TVET teachers. A shortage of TVET teachers is arguably a part of the “tradition” of the TVET system. For many years, universities developing new programs for initial TVET teacher education to tackle this problem. However, this has led to a non-transparent structure of degree programmes on offer. This article presents, as a result of a qualitative research approach, a typology of initial TVET teacher education programmes in order to provide more transparency in the TVET teacher education system. Basis for the presented typology are the information provided by all universities in Germany (N=52) who offer vocational teacher education programmes. These information were then run through a criteria matrix, resulting in a typology of seven different study models. In conclusion, we can see that traditional models, while being offered the most in German universities, are challenged by a lot of different study models who are generally not considered traditional.